1999
DOI: 10.1046/j.1365-2478.1999.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

The problem of velocity inversion in refraction seismics: some observations from modelling results

Abstract: The applicability of seismic refraction profiling for the detection of velocity inversion, which is also known as a low‐velocity layer (LVL), is investigated with the aid of synthetic seismogram computations for a range of models. Our computational models focus on the inherent ambiguities in the interpretation of first‐arrival time delays or ‘skips’ in terms of LVL model parameters. The present modelling results reveal that neither the measure nor even the existence of a shadow zone and/or a time shift (skip) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In certain geological situations, a low‐velocity zone (LVZ) is inferred from a ‘shift’ in first arrivals (Whiteley & Greenhalgh 1979; Lutter et al 1994; Tewari et al 1995). Krishna et al (1999) showed that a shift in first arrivals is not necessarily an indicator of a LVZ. They suggest modelling the reflected phases from the top and bottom of the LVZ to solve the problem reliably.…”
Section: Introductionmentioning
confidence: 99%
“…In certain geological situations, a low‐velocity zone (LVZ) is inferred from a ‘shift’ in first arrivals (Whiteley & Greenhalgh 1979; Lutter et al 1994; Tewari et al 1995). Krishna et al (1999) showed that a shift in first arrivals is not necessarily an indicator of a LVZ. They suggest modelling the reflected phases from the top and bottom of the LVZ to solve the problem reliably.…”
Section: Introductionmentioning
confidence: 99%